Epidemiological Studies on Anaemia in Dogs in Anand, Gujarat - Panchal, Ronak; Rao, Neha; Raval, Sunant; Sadhu, Dasharath; Bharai, Munja (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present work was carried out to study the incidence and etiologies of anaemia in dogs. Out of a total of 1516 dogs presented at the  Veterinary Clinical Complex of the College in Anand, 127 (7.86%) dogs were found with anaemia. These anaemic dogs were selected to  detect etiologies of anaemia. The highest incidence of anaemia was due to haemorrhagic gastroenteritis (22.05 %) followed in descending  order by organopathy (20.47 %), ectoparasitic infestations (15.75%), viral infections (14.96%), iron deficiency (7.87%), rickettsia infections  (7.09%), endo-parasitic infections (6.30%), haemoprotozoa infections (2.36 %), pyometra (1.57%), drug and vaccine-associated cause  and tumour (0.79%, each). The different etiologies studied in relation to age, sex, and different breed also revealed anaemia mainly due  to parasites and haemorrhagic gastroenteritis in puppies and organopathy in older dogs, with a higher prevalence of haemorrhagic  gastroenteritis followed by organopathy in both the sexes and also higher incidence in Labrador Retriever and nondescript breeds. This  trend suggests the ameliorative measures that should be taken up on priority to prevent the occurrence of anaemia in dogs, particularly  puppies and older dogs, and in males than the females.
Keywords: Anaemia; Dogs; Etiology; Haematology; Incidence; Parasitic screening